TENDENCIES OF CHANGES IN MARKET BEHAVIOURSOF PHYSICALLY DISABLED CONSUMERS - Magdalena Maciaszczyk (Polityki Europejskie, Finanse i Marketing)
The article is a literature review and concerns the issue of tendencies of changes noticed in market behaviours of both healthy and physically disabled consumers. It is essential to notice that the way of making decisions and making choices is possibly a result of growing consumer awareness of disabled people but also generation changes undergoing on the market. Such generation changes are resulting in modifications both in a system of values and in the way that market participants communicate. Additionally, continuous globalization and digitization determining the process of consumer behaviours are also important. Internet is more frequently chosen as an alternative method of a barrier-free cybernetic communication channel where consumers from different groups can interact in the marketplace. A medical condition of a customer is becoming completely irrelevant and extraneous as the interactivity and dynamics of market changes let everyone adjust the market offer to own requirements and wants. Globalization means that customers with motor disorders are no longer limited to local communities and therefore the interest of young disabled consumers in virtual communities is growing.